Pediatric efficacy and safety in common cold treated with herbal medicine (PEACH): a systematic review and meta-analysis - Kim, Soo-Dam; Lee, Su Won; Woo, Seong-Cheon; Kim, Dong-Hyeon; Jun, Lee Keon; Kim, Jong-Hee; Yang, Dong-Yeol; Kang, Byung-Gab; Park, Yang-Chun; Lee, Boram; Lyu, Yee Ran (Frontiers in Pharmacology, 2026)
IntroductionThe common cold is one of the most frequent illnesses in children, yet effective and safe treatments remain limited. Concerns regarding the safety of conventional medications persist. Herbal medicine (HM) has long been used, but the quantity and certainty of evidence in children have not been systematically summarized.MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) following PRISMA guidelines (PROSPERO CRD42024610421). Nine databases were searched to October 2024. Eligible studies included pediatric patients (<19 years) treated with oral HM compared with conventional medicine, placebo, or no treatment. Risk of bias was assessed with RoB 2, and certainty of evidence was rated using GRADE.ResultsSixty-six RCTs involving 7,176 participants were included. HM significantly improved total effective rate compared with conventional medicine (RR = 1.16, 95% CI [1.12–1.21]), with combination therapy providing additional benefits (RR = 1.17, 95% CI [1.13–1.22]). HM shortened overall symptom improvement time (SMD = −1.01, 95% CI [–1.41, −0.60]) and reduced total symptom severity (SMD = −0.80, 95% CI [–1.22, −0.38]) compared with conventional medicine. Both HM monotherapy and combination therapy demonstrated a markedly lower incidence of adverse events compared with conventional medicine (RR = 0.28, 95% CI [0.20, 0.40] and RR = 0.53, 95% CI [0.32, 0.88], respectively), with reported events being mild and mainly gastrointestinal. The certainty of evidence was predominantly moderate according to the GRADE assessment, increasing confidence in these findings.ConclusionHM appears effective and safe for pediatric common cold, providing faster recovery and fewer adverse events. These findings, supported by moderate-certainty evidence, justify consideration of HM in pediatric care, although further high-quality, multicenter RCTs are needed.Systematic Review Registerationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=610421, identifier CRD42024610421.